Leaf Morphological Response of Several Dendrobium Orchids due to Colchicine Application - Windhiana Windhiana; Dwi Sucianingtyas Sukamto; Fatimatuz Zuhro (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Dendrobium orchid is an ornamental plant that has a relatively stable market and does not depend on the season. The increasing public demand for Dendrobium orchids is an opportunity to improve the character and quality of Dendrobium orchids, one of which is by inducing mutations through the application of colchicine. This study aims to determine the effect of orchid varieties and colchicine application on the morphology of Dendrobium orchid leaves. This research was conducted at the Sriwijaya Orchid Gallery Cluster B9, Jember. This study used a 2 factorial Randomized Block Design (RBD). The first factor was the treatment of varieties consisting of Dendrobium Venus Purple Algis (ALG) and Dendrobium Transient Pink Frederika (FRD), the second factor was the treatment of colchicine concentrations (0 ppm or control, 4000 ppm, 5000 ppm and 6000 ppm). The results of this study indicated that the application of colchicine had a significant effect on several leaf morphological characters, namely leaf length, width, and color. The best leaf length was obtained at a concentration of 5000 ppm, the best leaf width was obtained at a control concentration of 0 ppm, and the most intense leaf color was obtained at a colchicine concentration of 6000 ppm.